The world economy will need even more globalization in the post-pandemic 2021 decade - Contractor, Farok J. (Journal of International Business Studies, 2022)
Instead of the dire predictions of a post-pandemic world characterized by increased global risks, decoupling of economies, shake-up of global value chains, and the retreat of globalization, this article proposes that the changes induced by heightened nationalism and protectionism will be marginal rather than fundamental in nature. These marginally higher risks can easily be handled and ameliorated by multinational enterprises through alternate cross-border business strategies and emerging technologies. Moreover, the paper gives reasons why the future world economy will need even more globalization.